The functions of microparticles in pre-eclampsia. - van der Post, J; Lok, C; Boer, K; Sturk, A; Sargent, I; Nieuwland, R (2011)
Pre-eclampsia (P-EC), a heterogenic multisystem disorder characterized by hypertension and proteinuria, usually develops in the second half of pregnancy. The incidence is 2 to 5%, and P-EC is therefore a major cause of maternal and perinatal morbidity and mortality. Although the exact etiology is unknown, placental factors released into the maternal circulation lead to systemic maternal inflammation and endothelial dysfunction. Growing evidence indicates that placenta-derived microparticles, best known as syncytiotrophoblast microparticles (STBM), are important among these factors. This review provides an overview of the presence and function(s) of STBM and other cell-derived microparticles and exosomes.